The association between malaria and iron status or supplementation in pregnancy: a systematic review and meta-analysis. - Laura Sangaré; Anna Maria van Eijk; Feiko O Ter Kuile; Judd Walson; Andy Stergachis (PLoS ONE)
Introduction Malaria prevention and iron supplementation are associated with improved maternal and infant outcomes. However, evidence from studies in children suggests iron may adversely modify the risk of malaria. We reviewed the evidence in pregnancy of the association between malaria and markers of iron status, iron supplementation or parenteral treatment. Methods and findings We searched MEDLINE, EMBASE, the Cochrane Central Register of Controlled Trials, the Global Health Library, and the Malaria in Pregnancy library to identify studies that investigated the association between iron status, iron treatment or supplementation during pregnancy and malaria. Thirty one studies contributed to the analysis; 3 experimental and 28 observational studies. Iron supplementation was not associated with an increased risk of P. falciparum malaria during pregnancy or delivery in Africa (summary Relative Risk = 0.89, 95% Confidence Interval (CI) 0.66-1.20, I(2) = 78.8%, 5 studies). One study in Asia reported an increased risk of P. vivax within 30 days of iron supplementation (e.g. adjusted Hazard Ratio = 1.75, 95% CI 1.14-2.70 for 1-15 days), but not after 60 days. Iron deficiency (based on ferritin and C-reactive protein) was associated with lower odds for malaria infection (summary Odds Ratio = 0.35, 0.24-0.51, I(2) = 59.2%, 5 studies). With the exception of the acute phase protein ferritin, biomarkers of iron deficiency were generally not associated with malaria infection. Conclusions Iron supplementation was associated with a temporal increase in P vivax, but not with an increased risk of P. falciparum; however, data are insufficient to rule out the potential for an increased risk of P. falciparum. Iron deficiency was associated with a decreased malaria risk in pregnancy only when measured with ferritin. Until there is more evidence, it is prudent to provide iron in combination with malaria prevention during pregnancy.